2011
DOI: 10.1002/asia.201100638
|View full text |Cite
|
Sign up to set email alerts
|

Triclabendazole: An Intriguing Case of Co‐existence of Conformational and Tautomeric Polymorphism

Abstract: The crystal polymorphism of the anthelmintic drug, triclabendazole (TCB), is described. Two anhydrates (Forms I and II), three solvates, and an amorphous form have been previously mentioned. This study reports the crystal structures of Forms I (1) and II (2). These structures illustrate the uncommon phenomenon of tautomeric polymorphism. TCB exists as two tautomers A and B. Form I (Z'=2) is composed of two molecules of tautomer A while Form II (Z'=1) contains a 1:1 mixture of A and B. The polymorphs are also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…In this orientation, the disulfide exchange is not possible. On the other hand, the reaction between a thiol and the maleimide proceeds through the conjugation addition mechanism, also called Michael addition . In the current situation, the enone carbonyl of N ‐ethylmaleimide probably interacts with the metal center through a hydrogen bond with the bridging water, which not only stabilizes the configuration required for nucleophilic addition by the Cys105 thiol group, but also makes it more electrophilic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this orientation, the disulfide exchange is not possible. On the other hand, the reaction between a thiol and the maleimide proceeds through the conjugation addition mechanism, also called Michael addition . In the current situation, the enone carbonyl of N ‐ethylmaleimide probably interacts with the metal center through a hydrogen bond with the bridging water, which not only stabilizes the configuration required for nucleophilic addition by the Cys105 thiol group, but also makes it more electrophilic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Terada et al observed four conformational polymorphs of furosemide− nicotinamide 1:1 cocrystal [112]. A thermodynamic stability study of [116] Anthranilic acid (2) Packing Celecoxib [117] 4,4′-Bipyridine (BPY) (2) Packing Celecoxib [117] 1,2-Di(4-pyridyl) ethylene (DPE) (2) Packing Celecoxib [117] 1,2-Bis(4-pyridyl)ethane (BPE) (2) Packing Salicylic acid [118] N, N′-diacetylpiperazine (2) Packing Piroxicam [119] 4-Hydroxybenzoic acid (2) Tautomer Triclabendazole [120] 3,5-Dihydroxybenzoic acid (DHBA), 3,5-dinitrobenzoic acid (DNBA), oxalic acid, succinic acid, fumaric acid, 3,5-dinitrosalicylic acid (DNSA), maleic acid, adipic acid, glutaric acid, malonic acid (MA), salicylic acid (SA), and aspirin.…”
Section: Conformational Polymorphsmentioning
confidence: 99%
“…One of the polymorphs shows the piroxicam molecule as the zwitterionic form, whereas the other contains it as the non-ionized form [119]. Desiraju et al carried out several cocrystallization experiments on triclabendazole with several co-formers which included dihydroxybenzoic acid, dinitro benzoic acid, dinitro salicylic acid, oxalic acid, fumaric acid, succinic acid, glutaric acid, maleic acid, malonic acid, adipic acid, aspirin and salicylic acid [120]. This resulted in nine cocrystals of which two cocrystals were found to be tautomer A and the other seven cocrystals existed as tautomer B [120].…”
Section: Tautomeric Polymorphsmentioning
confidence: 99%
“…In other words, the different crystal structures show modulations at the molecular level within the same crystal packing. As the forms contain different amounts of tautomeric structures they can be classified as tautomeric polymorphs, a pair of polymorphs [67,68].…”
Section: Solid Solution Strengtheningmentioning
confidence: 99%